Victory Lane - Earnhardt, Crystal; Nang ChanYeema (Hagerstown, Maryland USA Review and Herald Publishing Association, 2003)
The story of John Earnhardt from the son of a bootlegger, to race car driver, to evangelist.
Keywords: Young Adult